The effect of family-oriented neuropsychological training interventions on marital incompatibilities and cognitive-emotional regulation of married clients addicted to drugs - Hanieh Goli Rostami; Saeed Pournagash Motlaq Tehrani; Fereydoun Yariari; Gholamali Afrooz (مجله علوم روانشناختی)
Background: One of the common problems in the families of drug addicts is marital incompatibility and cognitive-emotional regulation. One of the effective treatments for marital incompatibility and cognitive-emotional regulation is family-oriented neuropsychological training. Aims: The purpose of the present study was to determine the effect of family-oriented neuropsychological training interventions on marital incompatibility and cognitive-emotional regulation of married clients addicted to drugs. Methods: The present study was a descriptive interventional and semi-experimental design with a (pre-test-post-test with control group) and 3-month follow-up. The statistical population included all the married male clients addicted to narcotics admitted to the neuropsychiatric department of Kausar Semnan Hospital in Betveen 2022 and 2023 and considering the entry and exit criteria and available methods, 30 people were selected as a sample.. The tools of data collection were the standard questionnaires of marital discord by Spanier (1976) and cognitive regulation of emotion by Granfsky et al. (2001). The validity of these questionnaires was confirmed and reliability was calculated through Cronbach's alpha coefficient (0.93, 0.88 percent), respectively. For data analysis, descriptive (mean and standard deviation) and inferential (Kolmogorov Smirnov and univariate analysis of covariance) were done using SPSS24 and EXCEL software. Results: Family-centered neuropsychological training interventions have an effect on marital incompatibility and cognitive-emotional regulation of married drug dependent clients. Conclusion: The effect of family-centered neuropsychological training interventions on marital incompatibility and cognitive-emotional regulation of married clients dependent on drugs is powerful.